Uwarunkowania ubezpieczenia odpowiedzialności cywilnej pracowników branży paliwowej w Polsce - Wieteska, Stanisław; Celczyńska, Anna (Annales. Etyka w Życiu Gospodarczym, 2019)
In Poland, we have approx. 10,000 fuel stations and fuel depots. Approximately 27 million vehicles registered in Poland and several million vehicles transiting through Poland use the petrol stations. Petrol and LPG stations are very dangerous places with flammable materials. Hence, an important element is the civil liability of employees of petrol stations and fuel and LPG depots. The article presents the scale and types of threats that may occur during the operation of these facilities, and the security elements of this type of place are also discussed. The final part of the article presents the basic elements of liability insurance for petrol operators. The basic elements of this insurance are indicated, such as the scope of the liability, the contribution, the guarantee sum and the problems with settling claims.